Systemic oxidative DNA and RNA damage are not increased during early phases of psychosis: A case control study. (30th July 2016) - Nordholm, Dorte; Poulsen, Henrik Enghusen; Hjorthøj, Carsten; Randers, Lasse; Nielsen, Mette Ø.; Wulff, Sanne; Krakauer, Kristine; Nørbak-Emig, Henrik; Henriksen, Trine; Glenthøj, Birte; Nordentoft, Merete
Abstract: It has been suggested that patients with schizophrenia develop higher levels of oxidative stress, which may contribute to deteriorating mental illness. In order to examine oxidative stress in the early stages of severe mental illness, we examined the levels of systemic Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA) oxidation, 8-oxo-7, 8-dihydro-2′-deoxyguanosine and 8-oxo-7, 8-dihydroguanosine, perceived stress and recent life events in patients at ultra high-risk (UHR) of developing psychosis, in antipsychotic naïve patients with first-episode schizophrenia (FES), and in healthy controls. We included 41 UHR patients, 35 FES patients, and 29 healthy controls. There was no difference in the level of DNA/RNA oxidative damage between UHR patients and FES patients compared with healthy controls. We found no association between levels of DNA/RNA oxidative damage and perceived stress/life events. Based on the results, we suggest that DNA and RNA oxidative markers are not increased during the early stages of illness, but further longitudinal studies in first-episode psychosis should be carried out to examine whether DNA and RNA oxidative damage are potential markers of severe illness. Highlights: Patients experienced more perceived stress and life events than the healthy controls. DNA and RNA oxidative markers are not increased during the early stages of psychosis. No association between DNA/RNA oxidative damage and perceived stress/life events.